GENERAL CONSIDERATIONS ABOUT STATISTICAL POWER STUDIES - Bono, Roser; Arnau Gras, Jaume (Anales de Psicología / Annals of Psychology)
Due to the increasing importance of power analysis in behavioral sciences and to the fact that the available literature on the subject has been scarce and ambiguous for decades, the objective of this study is to provide the basic conceptual framework of statistical analysis of power. For this purpose, an historical review is made of the subject, and the most relevant aspects of the elements which directly influence power are discussed: sample size, significance level and effect size.